Principles and Practice of Lacrimal Surgery - Javed Ali, Mohammad (Springer India : Imprint: Springer, 2015)
Lacrimal disorders are one of the very common conditions encountered not only by the oculoplastic surgeons but also by the general ophthalmologists in their daily practice. Written by global experts in the field of dacyrology, this book is a comprehensive, updated practical guide on evaluation and management of patients with lacrimal diseases. This up-to-date reference work covers all aspects of the field including the basic anatomy and underlying pathology, evaluation of a patient, and all surgical procedures currently used in managing various disorders in an organized fashion. Surgical modalities including the endoscopic approaches are thoroughly and succinctly reviewed with ample illustrations for better understanding. Since familiarity with a surgical technique is incomplete without the knowledge of risk factors and red flags, an emphasis on dealing with surgical complications and failure has received priority in this treatise. Controversial topics and treatment dilemmas have been discussed in detail with the objective of reviewing the present consensus among the experts.